The Assessment of Sleep Quality and Insomnia Severity in Cardiovascular Diseases - Chaitra, Dhontha; Manasa, Kampelli; Puneem, Usha Sree; Peravena, Santosh Kumar; Kurapati, Madhu; Murthy, Sindgi Vasudeva (Indian Journal of Pharmacy Practice)
Background: Presence of altered sleep quality in cardiovascular disease proceeds to worsen the disease burden and shows an impact on quality of life. The aim of the study is to assess the sleep quality and insomnia severity in cardiovascular diseases and to determine the correlation between sleep quality, insomnia and cardiovascular diseases. Materials and Methods: This is a prospective observational study conducted over a period of 6 months in subjects visited the cardiac care center with a diagnosis of cardiovascular diseases recruited and assessed for sleep quality and insomnia severity by using Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI) respectively. Results: A total of 203 patients were included in the study. Mean age of study population was 55.9 years. In this study male patients are more than the females in reporting cardiovascular complaints. The total percentage of poor sleep quality was found to be high among the study population and moderate severe insomnia in fewer cases. The present study found significant correlation between sleep quality and insomnia severity among Left Ventricular Dysfunction (LVD), Diabetes Mellitus (DM), diastolic BP and systolic dysfunction, diastolic dysfunction and stress. Conclusion: Alteration in sleep quality and severity of insomnia are prominent among cardiovascular disease subjects. There is a need for in-depth assessment of sleep quality and insomnia among various cardiovascular diseases to provide better patient care.
Keywords: Sleep quality; Insomnia severity; Cardiovascular diseases; ISI; PSQI.